Melatonin improves the removal and the reduction of Cr(VI) and alleviates the chromium toxicity by antioxidative machinery in Rhodobacter sphaeroides. (15th February 2023) - Mao, Hao-Tian; Chen, Lun-Xing; Zhang, Meng-Ying; Shi, Qiu-Yun; Xu, Hong; Zhang, Da-Yan; Zhang, Zhong-Wei; Yuan, Ming; Yuan, Shu; Zhang, Huai-Yu; Su, Yan-Qiu; Chen, Yang-Er
Abstract: Bioremediation with photosynthetic bacteria (PSB) is thought to be a promising removal method for hexavalent chromium [Cr(VI)]-containing wastewater. In the present study, Rhodobacter sphaeroides ( R. sphaeroides ) SC01 was used for the investigation of Cr(VI) removal in Cr(VI)-contaminated solution in the presence of melatonin. It was found that exogenous melatonin alleviated oxidative damage to R. sphaeroides SC01, increased Cr (VI) absorption capacity of cell membrane, and improved the reduction efficiency of Cr(VI) via the activation of chromate reductants. The results showed that melatonin could further promote the increase in Cr(VI) removal efficiency, reaching up to 97.8%. Furthermore, melatonin application resulted in 296.9%, 44.4%, and 69.7% upregulation of ascorbic acid (AsA), glutathione (GSH), and cysteine (Cys) relative to non-melatioin treated R. sphaeroides SC01 at 48 h. In addition, the resting cells, cell-free supernatants (CFS), and cell-free extracts (CFE) with melatonin had a higher Cr(VI) removal rate of 18.6%, 82.0%, and 15.2% compared with non-melatonin treated R. sphaeroides SC01. Fourier transform infrared spectroscopy (FTIR) revealed that melatonin increased the binding of Cr(III) with PO4 3− and CO groups on cell membrane of R. sphaeroides SC01. X-ray diffractometer (XRD) analysis demonstrated that melatonin remarkably bioprecipitated the production of CrPO4 ·6H2 O in R. sphaeroides SC01. Hence, these results indicated that melatonin plays the important role in the reduction and uptake of Cr(VI), demonstrating it is a great promising strategy for the management of Cr(VI) contaminated wastewater in photosynthetic bacteria. Graphical abstract: Image 1 Highlights: Melatonin alleviated Cr(VI)-induced oxidative damage in Rhodobacter sphaeroides SC01. Melatonin increased the absorption capacity of R. sphaeroides SC01 to Cr(VI). Melatonin improved Cr(VI) reduction via non-enzymatic reduction pathways in R. sphaeroides SC01. Melatonin-mediated Cr(VI) removal mechanism was deduced in R. sphaeroides SC01.